BUSINESS JUDGEMENT RULE KAITANNYA SEBAGAI UPAYA PERLINDUNGAN HUKUM BAGI DIREKSI DALAM PENGELOLAAN INVESTASI BUMN (Studi Putusan Mahkamah Agung Nomor 121 K/Pid.Sus/2020) - Zulfikar, Rifqi Nur; Muryanto, Yudho Taruno (Jurnal Privat Law, 2025)
This article examines the regulations related to the Business Judgment Rule in Indonesia in providing legal protection for BUMN directors for the management of BUMN investments and the application of the Business Judgment Rule principle in Supreme Court Decision Number 121 K/Pid.Sus/2020. This type of article is normative and descriptive in nature. The types of materials used are secondary data with primary and secondary legal materials, as well as non-legal materials or tertiary legal materials. Data collection techniques are carried out by downloading, copying and then reading, studying, reviewing, and analyzing primary legal materials such as laws, the Civil Code and other regulations, books, articles, journals related to the issues concerned. studied. Furthermore, the technical analysis used is the deduction method. The results of the study indicate that the regulation related to the Business Judgment Rule in Indonesia is contained in Law Number 40 of 2007 concerning Limited Liability Companies Article 97 paragraph (5). Second, the Supreme Court Decision Number 121 K/Pid.Sus/2020 acquitted Karen Agustiawan as the defendant on the grounds that the decision taken by Karen Agustiawan was a business action so it was included in the Business Judgment Rule.